2016
DOI: 10.1016/j.commatsci.2016.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band alignment at CuGaS2 chalcopyrite interfaces

Abstract: Cu-chalcopyrite semiconductors are commonly used as light absorbing materials on solar cell devices. The study of the heterointerfaces between the absorbent and the contact materials is crucial to understand their operation. In this study, band alignments of the heterojunctions between CuGaS 2 chalcopyrite and different semiconductors have been theoretically obtained using density functional theory and more advanced techniques. Band alignments have been determined using the average electrostatic potential as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Using a self consisted GW scheme based on Hedin's Coulomb hole and screened exchange (scCOHSEX) followed by a perturbative G 0 W 0 step, Aguilera et al, reported an energy gap of 2.65 eV for CuGaS 2 , in very good agreement with the experimental value [20]. Recently, we have done ab-initio DFT theoretical calculations using a modified screened hybrid Heyd-Scuseria-Ernzerhof functional (HSE06) to improve the GGA approximation, and we have obtained a band gap of 2.43 eV, which reproduces excellently the experimental value [21].…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…Using a self consisted GW scheme based on Hedin's Coulomb hole and screened exchange (scCOHSEX) followed by a perturbative G 0 W 0 step, Aguilera et al, reported an energy gap of 2.65 eV for CuGaS 2 , in very good agreement with the experimental value [20]. Recently, we have done ab-initio DFT theoretical calculations using a modified screened hybrid Heyd-Scuseria-Ernzerhof functional (HSE06) to improve the GGA approximation, and we have obtained a band gap of 2.43 eV, which reproduces excellently the experimental value [21].…”
Section: Introductionsupporting
confidence: 83%
“…Recently, we have carried out ab-initio calculations of the structural and electronic properties of these materials, and the results obtained were reported in reference [21]. From the reference of Castellanos et al [21], we observe that the obtained values for the band gap is 2.43 eV for the CuGaS 2 , and 2.65 eV for the CuAlSe 2 .…”
Section: Electronic Structure Of Cugas 2 and Cualsementioning
confidence: 89%
See 3 more Smart Citations